1998
DOI: 10.1017/s0022215100142410
|View full text |Cite
|
Sign up to set email alerts
|

Study of ethmoid sinus involvement in multibacillary leprosy

Abstract: The nasal mucosal involvement in lepromatous leprosy is well recognized. Currently interest has centred around the involvement of paranasal sinuses in leprosy. They act as a reservoir and constant source of reinfection to the nasal mucosa. In the present prospective study 25 untreated patients with multi-bacillary leprosy were included. Clinical examination, computed tomography (CT) scan of paranasal sinuses, ethmoid sinus endoscopy and biopsy were carried out in all patients, to investigate the involvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Other factors may also become involved at later stages of infection. Thus, the influence of M. leprae on the upper respiratory tract often manifests itself as swelling, ulceration, perforation, or the collapse of septal cartilage and paranasal sinuses 14 . Peripheral nerve infiltration, motor and sensory abnormalities, autonomic nerve dysfunction, and ganglia infiltration have been reported in leprosy patients 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Other factors may also become involved at later stages of infection. Thus, the influence of M. leprae on the upper respiratory tract often manifests itself as swelling, ulceration, perforation, or the collapse of septal cartilage and paranasal sinuses 14 . Peripheral nerve infiltration, motor and sensory abnormalities, autonomic nerve dysfunction, and ganglia infiltration have been reported in leprosy patients 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…2,7,8 On the other hand, a previous study of treated lepromatous leprosy patients found septal perforation in 47.3 per cent (18 of 38), suggesting that, in cases of persistent infection, cartilage destruction may continue even after the treatment of leprosy. Lepromatous leprosy is the severest type of leprosy, so we presumed that massive chronic granulomatous infection had caused these scar formations.…”
Section: Discussionmentioning
confidence: 93%
“…7,8 Similarly, the ethmoidal sinuses have been reported to be the most commonly involved sinuses (55.2 per cent) in treated lepromatous leprosy patients; furthermore, 33.3 per cent of these patients have had persistent acidfast bacilli infection. Ex-leprosy patients are sometimes exposed to antibiotics for management of the complications of leprosy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other changes affecting olfactory function occur in later stages of the disease. M. lepra causes edema, swelling, ulceration, septic perforation, and collapse at the upper respiratory tract [23]. Peripheral neuron infiltration, motor and sensorial abnormalities, autonomic nerve dysfunction, and ganglion infiltration have been reported in people who have leprosy [24].…”
Section: Discussionmentioning
confidence: 99%